Isolated cardiac sarcoidosis: A clinical challenge - Paul Njoku; Sumbal Rani; Orestis Paschalis; Emanuela Alati; Amit K.J. Mandal; Constantinos G. Missouris (Clinical Medicine)
Sarcoidosis is an inflammatory disease characterised by non-caseating granulomas of unclear aetiology. Isolated cardiac sarcoidosis (ICS) is rare and occurs when there is granulomatous infiltration of myocardial tissue without evidence of extracardiac sarcoidosis. The heterogeneity in clinical manifestations often presents a diagnostic challenge which leads to delays in treatment initiation. Our case highlights the often quiescent presentation of ICS, the importance of early treatment and the diagnostic challenges that contribute to its underdiagnosis.